Comprehensive index for community health assessment of typical district administrative units in Maharashtra State, India - Prakash Prabhakarrao Doke (Wolters Kluwer Medknow Publications, 2016)
Background: Health administrators require status of health of different administrative units under them. Use of large number of indicators may create confusion and uncertainty about health status. Availability of a comprehensive index is certainly useful.Objective: To evolve one comprehensive health index for a district as unit and measure district wise disparity.Materials and Methods: Ten indicators from categories of health outcomes, health system, determinants of health, and utilization of services were considered. Data for districts in Maharashtra State were obtained from different sources.For each indicator the best performing district was given score of 100 and other districts were given marks proportionately.Results: The comprehensive index for the state was 0.52. The district scoring lowest value of 0.36 was a tribal district and scoring highest value of 0.66 was a nontribal district.Conclusion: Computing such index of districts for monitoring and allocation of resources may be useful managerial tool.